2019
DOI: 10.1016/j.ijchp.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Parenting practices and adolescent social anxiety: A direct or indirect relationship?

Abstract: Background/Objectives According to existing evidence, parental educational practices and social anxiety are to some degree connected. However, the possibility that this relationship is an indirect one and is mediated by individual factors such as self-esteem or emotional regulation has not yet been explored. The aim of this study was therefore to explore the relationship between maternal and paternal educational practices and social anxiety, and test both the direct and the indirect pathways. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
3
28
0
3
Order By: Relevance
“…Non-democratic parenting styles such as authoritarian, permissive, neglectful inversely related to adolescent's low self-esteem [30,32,33]. Its in accordance with this study which showed the proportion of low self-esteem is frequently in non-democratic parenting styles.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Non-democratic parenting styles such as authoritarian, permissive, neglectful inversely related to adolescent's low self-esteem [30,32,33]. Its in accordance with this study which showed the proportion of low self-esteem is frequently in non-democratic parenting styles.…”
Section: Discussionsupporting
confidence: 87%
“…It is in accordance with this study which showed that less adolescent with democratic parent have low selfesteem than adolescent from non-democratic parent. Democratic parents provide discourse and insight into thinking process, doing activities and socializing well so as to encourage positive mental development, especially selfesteem [6,8,20,28,33].…”
Section: Discussionmentioning
confidence: 99%
“…The observed mediation process is very new and interesting because it suggests that the characteristics of parental socialization, in terms of acceptance and involvement as well as strictness and imposition, influence school victimization, mainly because they previously influence their response in the social interaction of adolescents. Our findings could suggest that adolescents' perceptions of the socialization practices used by their parents not only influence the appearance, development, and maintenance of social anxiety [27,34,60], but also their relationships with their peers in the classroom, which would be an extension of the family system.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, these studies have associated social anxiety with a greater prevalence of this problem in classrooms [25,26]. However, it is important to note that most research has focused on clinical samples, and few studies have analyzed this problem in the school environment; hence, the lack of information in this regard [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…La existencia de conflicto en el hogar es un factor de riesgo para niños y adolescentes, especialmente cuando ocurre de manera frecuente, intensa y no se resuelve adecuadamente (Cutrín, Maneiro, Sobral, y Gómez-Fraguela, 2019;Gallego, Novo, Fariña, y Arce, 2019). Facilita la inadaptación psicológica (Camisasca, Miragoli, y Di Blasio, 2019), asociándose a largo plazo con problemas externalizantes, tal como agresividad, vandalismo, conductas desadaptadas, bajo rendimiento académico; e internalizantes, como síntomatología ansioso-depresiva, baja autoestima, o malestar psicológico (Gómez-Ortiz, Romera, Jiménez-Castillejo, Ortega-Ruiz, y García-López, 2019;Lucas-Tompson, Lunkenheimer, y Dumitrache, 2017;Yap y Jorm, 2015). Esto puede deberse a que los subsistemas marital y paterno-filial son predictores interdependientes de la gestión emocional de los menores (Frankel, Umemura, Jacobvitz, y Hazen, 2015).…”
unclassified